A modified heterotopic heart transplantation in the rat – as an important model in experimental regeneration and replacement of the failing organ - Śliwka, Joanna E.; Tyrpień, Mirosław; Wilczek, Piotr M.; Zembala, Marian; Przybyłowski, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2020)
The qualification of new knowledge is one of the oldest problems in experimental medicine that provides a link between fundamental discovery, hypothesis, ‘proof of concept’ preclinical studies and development of clinical trials. The biggest challenge in animal models is the proper evaluation of all the aspects that are crucial in specific studied pathologies as well as the prediction of their progression. The aim of this review was to describe and discuss the rat animal model of heart transplant. The rat model of heart transplantation is an excellent yet underestimated method of research of prevention, monitoring and treatment of acute and chronic, immune and nonimmune response to organ transplantation. Despite being a technically and logistically demanding model, it provides a tool for reproducible experiments with longterm animal survival and excellent graft survival.